NEEDS ANALYSIS OF MATHEMATICS EVALUATION TOOLS BASED ON WORDWALL WEBSITE AT SDN LALADON 02 BOGOR DISTRICT: Analisis Kebutuhan Alat Evaluasi Pembelajaran Matematika Berbasis Web Wordwall Di SDN Laladon 02 Kabupaten Bogor - Fadillah, Farid (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2024)
The research aims to determine the features needed by fourth grade students at SDN Laladon 02 in Bogor Regency in mathematics lessons by using an online assessment tool called Wordwall. The research method used is Research and Development (R&D) through qualitative and quantitative approaches (mix method). Development model based on Borg & Gall, with some modifications made by Sugiyono. This research only used 8 out of 10 research processes, due to limited time and adjusted to the needs of the research being carried out. The following 8 research steps were used: Gathering requirements, collecting data, designing the product, validating the design, revising the design, conducting initial product trials, revising the product, and using trials. Class IV students were research subjects using one to one evaluation with 3 students and small group evaluation with 10 to 15 students. The data collection process was carried out using a questionnaire. The results of the needs questionnaire show that teachers have not used interactive learning assessment tools in giving grades to students. Teachers still use traditional techniques such as written exams. Evaluation techniques are needed that can help students change their perspective on learning.